Pengaruh Kawasan Ekonomi Khusus terhadap Investasi Asing dan Peningkatan Lapangan Kerja di Indonesia - Hasanah, Tatun Uswatun (Jurnal EMT KITA, 2025)
This study aims to analyze the influence of Special Economic Zones (SEZs) on foreign investment and increased employment in Indonesia, as well as the mediating role of foreign investment in the relationship. This study uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with quantitative data obtained from respondents related to the management and implementation of SEZs. The results of the study indicate that SEZs have a positive and significant influence on foreign investment (β = 0.567, p < 0.001) and increased employment (β = 0.295, p = 0.003). In addition, foreign investment also has a positive effect on increased employment (β = 0.359, p = 0.001), and acts as a mediator in the relationship between SEZs and increased employment (β = 0.203, p = 0.001). These findings confirm that SEZs not only have a direct impact on job creation, but also indirectly through increased foreign investment. The implications of this study indicate that optimizing SEZs through more flexible policies, improving infrastructure, and empowering local workers can strengthen the attractiveness of SEZs for foreign investors and increase job creation. Therefore, the government and stakeholders need to develop a more comprehensive strategy in managing SEZs in order to provide greater economic benefits for Indonesia.